Sahara en mouvement - Dominique Casajus (L’Année du Maghreb)
What Fernand Braudel once said of the Mediterranean sea can be said of the Sahara desert: drawing up boundaries is a difficult task. However, some geographers attempted to do so, and their endeavors were part of what may be termed the “invention” of the Sahara. In our introduction we pointed out some key figures of this invention (Leo Africanus, Eugene Daumas, Emile Carette, Henri Duveyrier, Robert Capot-Rey ...) then briefly presented the various contributions to the project, from a historical perspective. Indeed the Sahara-inspired dreams of today’s solar engineers are every bit as wild as the utopias of technicians from the colonial era. Similarly, the rumors fueled by media about AQIM are not very different from those once spread about the Senussi brotherhood. In the same way, the political thinking of the Tuareg in Mali and Niger is not so far remote from the thinking of the Moorish scholars of the seventeenth through nineteenth centuries. And again, the current migrations in the Sahara desert were preceded by other migrations, even if those took place under the duress of the slave trade. We cannot say that the Sahara has remained unchanged for centuries, but the movements and ideas that travel through it were not born yesterday.